Standardisasi sarana dan prasarana dalam pengembangan sekolah di SDIT Muhammadiyah Al-Kautsar - Prestysa, Jahar Ahlian; , Honest Ummi K, S.S., M. Hum (2017)
This study aims to describe the: 1) Standardization and infrastructure based on the law regulation of the Minister of national education of 24 of 2007, Number 2) management and infrastructure, 3) Barriers experienced in managing infrastructure, 4) solutions are taken to overcome the problems experienced, and 5) and infrastructure management role in the development of the school. This type of research is qualitative research design case studies. Data collection techniques used are interviews, observation, and documentation. Data were analyzed through an interactive analysis that includes data collection, data presentation, data reduction, and the withdrawal of the conclusion. The technique of the validity of the data is done by triangulation triangulation methods and sources. The results showed that: 1) Standardization and infrastructure advice on SDIT Muhammadiyah Al-Kautsar already meet the law regulation of the Minister of national education of 24 Numbers in 2007 about education standards such as classrooms, principal, teacher's room, INFIRMARY, library, playground/sports, shed, Privy, and circulation. 2) management and infrastructure are all submitted to the Deputy Head of school infrastructure section along with her team to manage the infrastructure include: planning, procurement, storage, maintenance, supervision, budgeting, inventory, and removal infrastructure, 3) lack of supplies infrastructure library and place too narrow, 4) vice principal parts and infrastructure planning has to restructure the space library with complete equipment necessary and expand future room , 5) the role of management and infrastructure development in schools is very influential, because management of the facilities and infrastructure that will either advance the quality/quatity of schools with various achievements, thus luring the elderly learners to send his son in SDIT Muhammadiyah Al-Kautsar .